Designing a test battery for health-related physical measurements as a tool for selecting students for sports teams - Benabid, Anouar; Tahar, Zeghib Mohamed (The International tax journal, 2025)
The sports selection process is a systematic, scientific endeavour with an objective foundation that considers athletes’ morphological, physiological, psychological and environmental aspects, with the aim of identifying individuals who are most compatible with the requirements of sports activities. Selection is based on physical and health measurements that predict an individual’s physical abilities and direct them towards the sports specialisation that best matches their potential. This process comprises integrated stages, including preliminary, specific, and qualifying selections, supported by leading scientific models such as the Gimbel, Drake, and Barr-Or models, which provide precise execution guidelines for selection programmes. Individual differences among athletes result from the interaction of genetic and environmental factors that determine structural and functional traits, directly influencing physical and psychological performance during training and competition. This article uses the example of a football player to highlight the essential qualities required for optimal performance, integrating physical, technical, and psychological requirements. Elements of physical fitness, such as endurance, muscular strength, speed and agility, form the basis for developing motor skills and enhancing overall sports performance. Effective sports selection integrates modern scientific knowledge and field application to ensure the identification and development of promising talent in a balanced training environment.